Expression of kiwifruit-derived actinidin in Nicotiana benthamiana leaves - Kang, Ji Hyun; Lee, Jae-Ho; Lee, Dong Wook (Frontiers in Plant Science, 2025)
Kiwifruit (Actinidia deliciosa)-derived actinidin, a cysteine protease, is renowned for its meat-tenderizing and milk-clotting activities. Despite its potential in various biotechnological applications, an efficient expression platform for actinidin production has not yet been developed. Instead, actinidin has traditionally been purified directly from the fruits of various plants. This study aimed to produce kiwifruit-derived actinidin in the leaves of Nicotiana benthamiana. The expressed actinidin was directed to the lumen of the endoplasmic reticulum (ER) using the binding immunoglobulin protein (BiP) signal sequence and an ER retention signal. To facilitate cost-effective purification, the family 3 cellulose-binding module (CBM3) was employed as an affinity tag, along with microcrystalline cellulose beads that bind efficiently to CBM3. A significant portion of the expressed actinidin was recovered in the soluble fraction without proteolytic degradation. The purified actinidin exhibited β-casein-degrading activity, with optimal efficiency observed at 55°C and pH 7.0. These results establish a promising plant-based platform for the efficient production and functional application of kiwifruit-derived actinidin in diverse biotechnological processes.